The Impact of Covid-19 Pandemic on Child Routine Immunization Programs: A Systematic Review - Safira Smaradhana; Iche Andriany Liberty (Sriwijaya Journal of Medicine, 2023)
Immunization is one of the most successful, most accepted and proven cost-effective public health preventive interventions in the world and has saved 2 to 3 million children from immunization-preventable diseases.  The COVID-19 outbreak and the effort being made to overcome the outbreak could cause negative impacts on the utilization of basic immunization services. During the outbreak, basic immunization coverage rate in various regions had decreased. This article conducted a comprehensive and systematic literature search in electronic databases (PubMed, ScienceDirect, Sage Journal, SpringerLink, ClinicalKey, and Oxford Academic) with articles published in the last 5 years and adjusted according to inclusion and exclusion criteria. This systematic review use PRISMA (Preferred, Reporting Items for Systematic Review and Meta-analysis). There were 2 studies that met the final inclusion criteria. The results showed a significant reduction of basic immunization coverage happen especially during the early period of pandemic.  Six themes are identified related to the decrease: 1) Covid-19 lockdown; (2) motivation for childhood immunization; (3) availability of biosafety procedures and personal protective equipment (PPE); (4) service adjustments and guidelines during the pandemic; (5) the availability of vaccines; and (6) the resilience of the immunization program in view of COVID-19. Childhood routine immunization coverage rate significantly decreased during the early period of the pandemic.  Interventions for providers and parents is required to ensure adequate catch-up of delayed/missed immunizations in order to prevent potential outbreaks of vaccine-preventable diseases.